2000
DOI: 10.1089/oli.1.2000.10.177
|View full text |Cite
|
Sign up to set email alerts
|

A Cationic Derivative of Amphotericin B as a Novel Delivery System for Antisense Oligonucleotides

Abstract: A novel approach based on a plasma membrane permeability-disturbing agent was proposed as an antisense oligonucleotide delivery system. AMA, a derivative of the polyene antibiotic amphotericin B, formed a stable complex when mixed with phosphodiester oligodeoxynucleotides and enhanced the intracellular uptake of a 5' fluoresceinated anti-mdr1 20-mer into NIH-MDR-G185 cells. The nonlabeled phosphorothioate form of the oligodeoxynucleotide, complexed to AMA, inhibited P-glycoprotein expression with better effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Current strategies to reverse MDR are based: (i) on the synthesis of new non‐cross resistant cytostatics (Antonini et al ., 1995; Bassan et al ., 1997; Kubota et al ., 1998; Stefańska et al ., 1999); (ii) on the identification of effective and more selective MDR reversing agents (chemosensitizers) (Raderer & Scheithaner, 1993; Pereira et al ., 1994; Mankhetkorn & Garnier‐Suillerot, 1996; Pascaud et al ., 1998; Berger et al ., 1999; Teodori et al ., 1999); (iii) on the selective inhibition of gene expression encoding ATP‐dependent export pump using antisense oligonucleotides (Alahari et al ., 1996; Stewart et al ., 1996; Garcia‐Chaumont et al ., 2000) or ribozymes (Palfner et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current strategies to reverse MDR are based: (i) on the synthesis of new non‐cross resistant cytostatics (Antonini et al ., 1995; Bassan et al ., 1997; Kubota et al ., 1998; Stefańska et al ., 1999); (ii) on the identification of effective and more selective MDR reversing agents (chemosensitizers) (Raderer & Scheithaner, 1993; Pereira et al ., 1994; Mankhetkorn & Garnier‐Suillerot, 1996; Pascaud et al ., 1998; Berger et al ., 1999; Teodori et al ., 1999); (iii) on the selective inhibition of gene expression encoding ATP‐dependent export pump using antisense oligonucleotides (Alahari et al ., 1996; Stewart et al ., 1996; Garcia‐Chaumont et al ., 2000) or ribozymes (Palfner et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Current strategies to reverse MDR are based: (i) on the synthesis of new non-cross resistant cytostatics (Antonini et al, 1995;Bassan et al, 1997;Kubota et al, 1998;Stefan ska et al, 1999); (ii) on the identi®cation of eective and more selective MDR reversing agents (chemosensitizers) (Raderer 1996;Garcia-Chaumont et al, 2000) or ribozymes (Palfner et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…AmA, a polyene antibiotic and a promising cationic vector, brings new possibilities toward efficient and suitable transport and following distribution of the modified oligonucleotide 13. B16 cells incubated with the mixture TMR‐dT 15 /AmA exhibit significantly enhanced intracellular oligonucleotide uptake.…”
Section: Resultsmentioning
confidence: 99%
“…In this experiments a 42 mer antisense against human APP. Amphotericin B was first used by us to transport DNA (Kumar et al, 1974) and later shown to be a valuable agent for the transport of oligonucleotides into 3T3 cells (Garcia-Chaumont et al, 2000). Using CaCl 2 or Amphotericin B would cause some cell death if we cross concentrations above 1mM and 10 µM respectively.…”
Section: Uptake Of Antisense Oligonucleotidesmentioning
confidence: 99%